Utilization of expander-extruder processed complete diet containing sorghum straw in Ongole bull calves - REDDY, G V N; REDDY, M R (The Indian Journal of Animal Sciences, 2012)
Expander-extruder processed sorghum-straw-based complete diet, corresponding mash diet and a conventional diet (containing concentrate mixture and chopped sorghum-straw) were evaluated in 18 Ongole bull calves (6 in Each group). DMI/100 kg body weight and water intake/kg DMI were similar on all the diets. Digestibilities of DM, OM and CP were significantly (P